Thin-wall injection molding polylactic acid composition as well as preparation method and application thereof

By adding heat-resistant modifiers, anti-warping agents and flow regulators to the polylactic acid material, the problems of low fluidity, slow crystallization, poor heat resistance and warping deformation during thin-wall injection molding are solved, and the efficient crystallization of the material, improving heat resistance and improving warping performance of the material is achieved.

CN119708784APending Publication Date: 2025-03-28LIANHONG (JIANGSU) NEW MATERIALS RES INST CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311263379.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing polylactic acid materials have problems such as low fluidity, slow crystallization, poor heat resistance and warping during thin-wall injection molding, which limits their application in disposable thin-walled products.

Method used

The compositions of polylactic acid 50-99%, toughener 1-20%, heat-resistant modifier 0.5%-40%, heat-resistant anti-warping agent 0.5%-30%, flow regulator 0.01%-25%, antioxidant 0.01%-1% and lubricant 0.01%-1% are used. By adjusting the amount of PDLA or glass flakes, the amount of branched PLA is adjusted, and the content of hyperbranched polyester and peroxide is controlled to improve the crystallization rate, heat resistance and warping resistance of the material.

Benefits of technology

It significantly shortens the molding cycle of polylactic acid materials, improves the heat resistance temperature and warpage resistance of the products, and meets the process requirements of thin-wall injection molding and the use requirements of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention provides a composition which comprises the following components in parts by weight: 50-99% of polylactic acid, 1-20% of a toughening agent, 0.5-40% of a heat-resistant modifier, 0.5-30% of a heat-resistant anti-warping agent, 0.01-25% of a flow regulator, 0.01-1% of an antioxidant and 0.01-1% of a lubricant. The composition can meet the technological requirements of PLA thin-wall injection molding and the use requirements of heat resistance and warping resistance of products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and specifically relates to a polylactic acid (PLA) composition and a preparation method and application thereof. Background Art

[0002] At present, disposable thin-walled products such as lunch boxes and milk tea cups are mainly made of PP. Thin-wall injection molding PP has the characteristics of light weight, easy integrated design, and short production cycle. With the rise of the takeaway market, the market demand has surged, and the consumption of thin-wall injection molding PP has exceeded one million tons. However, with the increasing attention of the country and people to environmental protection, the disadvantages of PP disposable tableware, such as huge consumption, difficult recycling, and difficult degradation, have emerged. And there is a possibility that disposable products will be restricted or prohibited from use. Using PLA, which can contact food, is degradable by microorganisms, and can be injection molded into thin-walled products, as food packaging and storage materials has become a new development trend. PLA is a bio-based material with biodegradable characteristics, and the production process has the advantage of low carbon emissions. Thin-wall injection molding has the characteristics of short molding cycle (5-10s for PP lunch boxes), and requires materials with high melt flow rate, good transparency, and high crystallization temperature. The current PLA raw material has low fluidity, and the crystallization and nucleation rates are both low. Its crystallization is very slow, which leads to a longer thin-wall injection molding cycle and poor heat resistance of the product. In-mold or out-of-mold crystallization is required to improve heat resistance. However, in-mold crystallization will significantly increase the molding cycle, which is not conducive to production and cost control. And out-of-mold crystallization will cause warping deformation due to heat crystallization of PLA, resulting in poor matching between the box body and the cover body. At the same time, due to the low crystallinity of PLA thin-walled products, the products have poor heat resistance, which limits the application field. These factors limit the large-scale promotion and application of PLA thin-wall injection molding.

[0003] Patent CN 112409646 A discloses a starch-based biodegradable plastic masterbatch for thin-wall injection molding. The masterbatch is added to bio-based plastics (PLA, PBAT, PCL, etc.) to prepare thin-wall injection molding materials. Since the masterbatch uses high-amylose starch, the fluidity is low and the material is opaque. It also does not solve the problem of slow crystallization of PLA and heat resistance of the product.

[0004] Patent CN 112694727 A discloses a fully biodegradable material for thin-wall injection molding and its preparation method, wherein the biodegradable polyester is 100 parts, the toughening agent is 8-10 parts, the solubilizing agent is 4-6 parts, and the inorganic filler is 20-30 parts. The patent uses low molecular weight toughening agents (diacetin, tributyl citrate, etc.) and solubilizing agents (p-toluenesulfonic acid, dibutyltin dilaurate, etc.), which leads to reduced heat resistance of thin-wall injection molding PLA and the possibility of precipitation of low molecular weight additives.

[0005] Patent CN 114773806 A discloses a degradable composite material for thin-wall injection molding and a preparation method thereof, wherein the materials used include 30-80 parts of biodegradable resin, 10-50 parts of toughening agent, 1-5 parts of flow promoter, 5-20 parts of degradable glass fiber, 1-5 parts of fiber surface treatment agent, 1-5 parts of compatibilizer, 5-20 parts of inorganic filling material, 0.2-1 parts of heat-resistant modification auxiliary agent and 0.1-0.8 parts of lubricant. The crystallization performance and heat resistance of the material are improved by adding degradable glass fiber and inorganic filling material, and the fluidity is adjusted by adding oligolactic acid. However, the degradable glass fiber has a large aspect ratio. During injection molding, the glass fiber will be oriented with obvious flow, resulting in inconsistent shrinkage rates of the material in the lateral direction (vertical flow direction) and longitudinal direction (flow direction), resulting in warping and deformation of the product after demoulding.

[0006] It can be seen that the current polylactic acid used for thin-wall injection molding has certain limitations and cannot fully meet the requirements of thin-wall injection molding and the use requirements of products. Summary of the invention

[0007] In order to develop a polylactic acid material that can meet the requirements of thin-wall injection molding processing and product use requirements, the present invention provides a composition, which includes, by weight, 50-99% of polylactic acid, 1-20% of a toughening agent, 0.5%-40% of a heat-resistant modifier, 0.5%-30% of a heat-resistant anti-warping agent, 0.01%-25% of a flow regulator, 0.01%-1% of an antioxidant and 0.01%-1% of a lubricant.

[0008] According to an embodiment of the present invention, the composition includes, by weight: 75-95% polylactic acid, 3-15% toughening agent, 3%-20% heat-resistant modifier, 3%-15% heat-resistant anti-warping agent, 0.1%-15% flow regulator, 0.1%-1% antioxidant and 0.1%-1% lubricant.

[0009] According to an embodiment of the present invention, the composition includes, by weight, 75-90% polylactic acid, 3-12% toughening agent, 3%-18% heat-resistant modifier, 3%-12% heat-resistant anti-warping agent, 5%-15% flow regulator, 0.1%-0.5% antioxidant and 0.1%-0.5% lubricant.

[0010] According to an embodiment of the present invention, the polylactic acid is PLLA (poly-L-lactic acid), preferably high optical purity PLLA, L optical purity ≥ 98%, and a melt index of 1-20 (190°C, 2.16kg); for example, Hisun E190, melt index 4g / 10min (190°C, 2.16kg), L optical purity > 99%, or Total Cobien L175, melt index 3g / 10min (190°C, 2.16kg), L optical purity > 99%.

[0011] According to an embodiment of the present invention, the toughening agent is branched polylactic acid PLLA, which has a number average molecular weight of 30,000-150,000 and a branching degree g'≤0.8, for example, the number average molecular weight is 98,000-102,000 and the branching degree g' is 0.58 or 0.76.

[0012] According to an embodiment of the present invention, the branched polylactic acid PLLA is prepared by the following method:

[0013] Four-arm branched polylactic acid was synthesized by melt ring-opening polymerization with L-lactide as raw material, stannous octoate (Sn(Oct)2) as catalyst and pentaerythritol (PET) as branching agent.

[0014] According to an embodiment of the present invention, the heat-resistant modifier is one of PDLA and glass flakes or a combination thereof. The PDLA is poly (d-lactic acid), preferably with a D optical purity of ≥98% and a melt index of 3-150 g / 10 min (190°C, 2.16 kg); for example, the PDLA is Total Cobien D070, with a melt index of 120 g / 10 min (190°C, 2.16 kg), and a D optical purity of >99%; or Total Cobien D120, with a melt index of 10 g / 10 min (190°C, 2.16 kg), and a D optical purity of >99%.

[0015] According to an embodiment of the present invention, the glass flakes have a thickness of 0.2-20 μm, preferably E-type glass flakes with a thickness of 0.5-10 μm and an average diameter of 100-1000 μm; for example, Japanese NSG REFG-101 with a thickness of 5 μm and an average diameter of 600 μm; or Japanese NSG MEG160FY-M01 with a thickness of 0.7 μm and an average diameter of 160 μm.

[0016] In one embodiment of the present invention, the heat-resistant modifier is a compound of PDLA and glass flakes.

[0017] According to an embodiment of the present invention, the heat-resistant and anti-warping agent is glass flakes with a thickness of 0.2-20μm, preferably E-type glass flakes with a thickness of 0.5-10μm and an average diameter of 100-600μm; for example, Japanese NSG REFG-101, with a thickness of 5μm and an average diameter of 600μm; or Japanese NSG MEG160FY-M01, with a thickness of 0.7μm and an average diameter of 160μm.

[0018] According to an embodiment of the present invention, the flow regulator is a branched polylactic acid PLLA, a hyperbranched polyester, and a combination of one, two or three of peroxide; preferably, the molecular weight of the branched polylactic acid is 30,000-150,000, and the degree of branching g′≤0.8; the peroxide is 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane; the acid value of the hyperbranched polyester is >300 mg KOH / g, preferably a branched aromatic polyester, such as HyPer C181, which has an acid value of 400 mg KOH / g.

[0019] According to an embodiment of the present invention, the branched polylactic acid acts as both a toughening agent and a flow regulator in the composition, that is, when calculating the weight proportions of the above components, the branched polylactic acid needs to be calculated twice.

[0020] According to an embodiment of the present invention, the flow regulator is a combination of branched polylactic acid, hyperbranched polyester and peroxide.

[0021] According to an embodiment of the present invention, the weight proportion of the flow regulator is 5-15%, preferably 5.4-10.4%. For example, the flow regulator is a composition of 5% BPLLA-1, 0.3% HyPer C181, and 0.1% 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane.

[0022] According to an embodiment of the present invention, in the composition, the total weight fraction of the hyperbranched polyester and the peroxide in the flow regulator is 0.3-1.0%, such as 0.4-0.9%, such as 0.4-0.6%, such as 0.4%.

[0023] For example, the flow regulator contains 0.3% by weight of hyperbranched polyester and 0.1% of peroxide; or contains 0.8% by weight of hyperbranched polyester and 0.1% of peroxide, or contains 0.3% by weight of hyperbranched polyester and 0.3% of peroxide.

[0024] According to an embodiment of the present invention, the antioxidant is one of antioxidant 1076 and antioxidant 168 or a combination thereof.

[0025] According to an embodiment of the present invention, the lubricant is an alkyd ester lubricant, preferably pentaerythritol stearate (PETS).

[0026] According to an embodiment of the present invention, the composition includes, by weight: 78-90% of Hisun E190 and / or Total L175, 3-12% of BPLLA-1 and / or BPLLA-2, 4-20% of heat-resistant modifier and heat-resistant anti-warping agent, the heat-resistant modifier and heat-resistant anti-warping agent are at least one of D070, D120, Japanese NSG REFG-101, and Japanese NSG MEG160FY-M01, 0.1%-0.4% of a composition of HyPer C181 and 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 0.1%-0.5% of antioxidant 1076 and / or antioxidant 168, and 0.1%-0.5% of lubricant PETS.

[0027] According to an embodiment of the present invention, the composition includes, by weight: 78-90% of Hisun E190 and / or Total L175, 5-10% of BPLLA-1 and / or BPLLA-2, 5-20% of heat-resistant modifier and heat-resistant anti-warping agent, the heat-resistant modifier and heat-resistant anti-warping agent are a combination of D070 and / or D120 and at least one of Japanese NSG REFG-101 and / or Japanese NSG MEG160FY-M01, 0.1%-0.4% of a composition of HyPer C181 and 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 0.1%-0.5% of antioxidant 1076 and / or antioxidant 168, and 0.1%-0.5% of lubricant PETS.

[0028] According to an embodiment of the present invention, the heat-resistant modifier and the heat-resistant anti-warping agent in the composition are a combination of D070 and / or D120 and at least one of Japanese NSG REFG-101 and / or Japanese NSG MEG160FY-M01.

[0029] The present invention also provides a method for preparing a degradable composite material for thin-wall injection molding using the above composition, comprising the following steps: polylactic acid, a toughening agent, a heat-resistant modifier, a heat-resistant anti-warping agent, a flow regulator, an antioxidant, and a lubricant are uniformly mixed according to a proportion, and then extruded and granulated.

[0030] According to an embodiment of the present invention, the method comprises: drying PLLA and PDLA in a vacuum oven, and then fully mixing the above substances in a high-speed mixer according to the above ratio, and then melt-extruding and granulating them through a twin-screw extruder to obtain a thin-wall injection molding PLA composition;

[0031] Among them, the temperature of each section of the barrel is: the temperature of the second section barrel is 135℃, the temperature of the third, fourth and fifth sections barrel is 200℃, the temperature of the sixth, seventh, eighth and ninth sections barrel is 190℃, the temperature of the ninth, tenth and eleventh sections barrel is 185℃, the head temperature is 180℃, the feeding frequency is 50 Hz, and the main engine speed is 200 rpm.

[0032] The present invention also provides a degradable composite material for thin-wall injection molding prepared by the above method.

[0033] According to an embodiment of the present invention, the degradable composite material for thin-wall injection molding can be used to prepare disposable thin-wall products such as lunch boxes and milk tea cups.

[0034] Beneficial Effects

[0035] The polylactic acid composition of the present invention can increase the crystallization rate and crystallinity of the material by adjusting the addition amount of PDLA or glass flakes, shorten the molding cycle, increase the heat resistance temperature of the product, and reduce the warping degree of the finished product. By adjusting the addition amount of branched PLA, the free volume of the molecular chain is increased to improve the impact resistance of the material and improve the toughness of the product. By adjusting the content of branched PLA, hyperbranched polyester or peroxide, the fluidity of the material is controlled to meet the requirements of different processes and products for fluidity. At the same time, the flow modifier can increase the distance between molecular chains and improve the mobility of molecular chains. It can also produce a synergistic effect with the heat-resistant modifier, while improving the fluidity of PLLA, promote the mutual diffusion of PLLA and PDLA to form stereoisomers, and improve the crystallization ability and heat resistance; while the flow modifier improves the fluidity of PLLA, it can reduce the injection temperature and pressure, reduce the residual internal stress of the product, and the flow modifier forms a synergistic effect with the heat-resistant anti-warping agent to reduce the warping degree of the product.

[0036] The composition can meet the process requirements of PLA thin-wall injection molding and the use requirements of heat resistance and warpage resistance of products. DETAILED DESCRIPTION

[0037] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technical schemes implemented, modified or adjusted based on the above content of the present invention are included in the scope of protection of the present invention.

[0038] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0039] The main raw materials and equipment used in the following examples and comparative examples include:

[0040] PLLA: Hisun E190, melt index 4g / 10min (190℃, 2.16kg), L optical purity>99%;

[0041] PLLA: Total Corbivir L175, melt index 3g / 10min (190℃, 2.16kg), L optical purity>99%; PDLA: Total Corbivir D070, melt index 120g / 10min (190℃, 2.16kg), D optical purity>99%; PDLA: Total Corbivir D120, melt index 10g / 10min (190℃, 2.16kg), D optical purity>99%; branched PLLA: homemade; BPLLA-1, Mn=98,000, branching degree g′=0.76;

[0042] BPLLA-2, Mn = 102,000, branching degree g′ = 0.58;

[0043] E-type glass flake: Japan NSG REFG-101, thickness 5μm, average diameter 600μm;

[0044] E-type glass flakes: Japan NSG MEG160FY-M01, thickness 0.7μm, average diameter 160μm;

[0045] E-type fiberglass: Jushi 534A;

[0046] Hyperbranched polyester: Wuhan Hyperbranched HyPer C181;

[0047] Antioxidant: commercially available 1076, 168;

[0048] Lubricant: Lonza PETS;

[0049] Extrusion granulation equipment: Coperion CTE35 twin-screw extruder;

[0050] Injection molding equipment: Haida injection molding machine HD280K model fast thin-wall injection molding machine.

[0051] Preparation method of branched polylactic acid (BPLLA-1):

[0052] Four-arm branched polylactic acid was synthesized by melt ring-opening polymerization with L-lactide as raw material, stannous octoate (Sn(Oct)2) as catalyst and pentaerythritol (PET) as branching agent.

[0053] Polymerization: Add 500g L-lactide and 5g pentaerythritol into a reactor, then add 1.5g stannous octoate as a catalyst, heat the reactor to 110°C to melt the monomers, stir at 100r / min for 5min, replace the air in the reactor with nitrogen, repeat the replacement-vacuuming three times, finally evacuate and fill with nitrogen, heat to 180°C for melt ring-opening polymerization, and end the reaction after 20h.

[0054] Purification: After the reaction is completed, 1L of chloroform is used to dissolve the polymer, and the material is discharged from the reactor after dissolution, and then 1.5L of chloroform is added to dilute the polymer and fully dissolve it. The polymer solution is added dropwise to ethanol in batches and stirred, and branched polylactic acid is precipitated, filtered, and vacuum dried at 60°C for 24 hours to obtain branched polylactic acid, which is marked as BPLLA-1.

[0055] Preparation method of branched polylactic acid (BPLLA-2):

[0056] The preparation and purification methods of branched polylactic acid (BPLLA-2) are the same as those of branched polylactic acid (BPLLA-1), the only difference being that the addition ratio of pentaerythritol (PET) is increased to adjust the branching degree. The addition amount of pentaerythritol is 7.5 g.

[0057] Characterization: Molecular weight, molecular weight distribution and intrinsic viscosity were determined by GPC-multi-angle laser scattering instrument-viscosity detector in chloroform phase. The degree of branching g' is the ratio of the intrinsic viscosity of branched PLA to the intrinsic viscosity of linear PLA with the same molecular weight (the relationship between molecular weight and intrinsic viscosity is obtained by fitting by measuring linear PLA with different molecular weights; the molecular weight and intrinsic viscosity obtained by GPC test of branched PLA can refer to the relationship between linear molecular weight and intrinsic viscosity to obtain the intrinsic viscosity of linear PLA with the same molecular weight, and the degree of branching g' is calculated).

[0058] Example 1

[0059] The PLA thin-wall injection molding material composition comprises the following components in parts by weight:

[0060] PLLA: E190; 84.2%;

[0061] Branched PLLA: BPLLA-1; 5%;

[0062] PDLA: D070; 5%;

[0063] E-type glass flake: REFG-101; 5%;

[0064] Hyperbranched polyester: HyPer C181; 0.3%;

[0065] Peroxide: 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane; 0.1%;

[0066] Antioxidants: 1076 and 168; 0.1% each;

[0067] Lubricant: PETS; 0.2%;

[0068] PLLA and PDLA were dried at 80°C in a vacuum oven for 6 hours, and then the above substances were fully mixed in a high-speed mixer according to the above ratio, and then melt-extruded and granulated by a twin-screw extruder to obtain a thin-wall injection molding PLA composition. Among them, the barrel temperature of each section is: the barrel temperature of the second section is 135°C, the barrel temperature of the third, fourth and fifth sections is 200°C, the barrel temperature of the sixth, seventh, eighth and eleventh sections is 190°C, the barrel temperature of the ninth, tenth and eleventh sections is 185°C, the head temperature is 180°C, the feeding frequency is 50 Hz, and the main engine speed is 200 rpm.

[0069] Example 2

[0070] The difference from Example 1 is that there is no PDLA, and the raw materials include the following components in parts by weight:

[0071] PLLA: E190; 89.2%;

[0072] Branched PLLA: BPLLA-1; 5%;

[0073] E-type glass flake: REFG-101; 5%;

[0074] Hyperbranched polyester: HyPer C181; 0.3%;

[0075] Peroxide: 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane; 0.1%;

[0076] Antioxidants: 1076 and 168; 0.1% each;

[0077] Lubricant: PETS; 0.2%.

[0078] Example 3

[0079] The difference from Example 1 is that there is no hyperbranched polyester and peroxide, and the raw materials include the following components in parts by weight:

[0080] PLLA: E190; 84.6%;

[0081] Branched PLLA: BPLLA-1; 5%;

[0082] PDLA: D070; 5%;

[0083] E-type glass flake: REFG-101; 5%;

[0084] Antioxidants: 1076 and 168; 0.1% each;

[0085] Lubricant: PETS; 0.2%.

[0086] Example 4

[0087] The difference from Example 1 is that there is no peroxide, and the raw materials include the following components in parts by weight:

[0088] PLLA: E190; 84.3%;

[0089] Branched PLLA: BPLLA-1; 5%;

[0090] PDLA: D070; 5%;

[0091] E-type glass flake: REFG-101; 5%;

[0092] Hyperbranched polyester: HyPer C181; 0.3%;

[0093] Antioxidants: 1076 and 168; 0.1% each;

[0094] Lubricant: PETS; 0.2%.

[0095] Example 5

[0096] The difference from Example 1 is that there is no hyperbranched polyester, and the raw materials include the following components in parts by weight:

[0097] PLLA: E190; 84.5%;

[0098] Branched PLLA: BPLLA-1; 5%;

[0099] PDLA: D070; 5%;

[0100] E-type glass flake: REFG-101; 5%;

[0101] Peroxide: 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane; 0.1%;

[0102] Antioxidants: 1076 and 168; 0.1% each;

[0103] Lubricant: PETS; 0.2%.

[0104] Example 6

[0105] The difference from Example 1 is that the amount of branched PLLA is increased, and the raw materials include the following components in parts by weight:

[0106] PLLA: E190; 79.2%;

[0107] Branched PLLA: BPLLA-1; 10%;

[0108] PDLA: D070; 5%;

[0109] E-type glass flake: REFG-101; 5%;

[0110] Hyperbranched polyester: HyPer C181; 0.3%;

[0111] Peroxide: 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane; 0.1%;

[0112] Antioxidants: 1076 and 168; 0.1% each;

[0113] Lubricant: PETS; 0.2%.

[0114] Example 7

[0115] The difference from Example 1 is that the amount of PDLA is increased, and the raw materials include the following components in parts by weight:

[0116] PLLA: E190; 79.2%;

[0117] Branched PLLA: BPLLA-1; 5%;

[0118] PDLA: D070; 10%;

[0119] E-type glass flake: REFG-101; 5%;

[0120] Hyperbranched polyester: HyPer C181; 0.3%;

[0121] Peroxide: 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane; 0.1%;

[0122] Antioxidants: 1076 and 168; 0.1% each;

[0123] Lubricant: PETS; 0.2%.

[0124] Example 8

[0125] The difference from Example 1 is that the amount of E-type glass flakes is increased, and the raw materials include the following components in parts by weight:

[0126] PLLA: E190; 79.2%;

[0127] Branched PLLA: BPLLA-1; 5%;

[0128] PDLA: D070; 5%;

[0129] E-type glass flake: REFG-101; 10%;

[0130] Hyperbranched polyester: HyPer C181; 0.3%;

[0131] Peroxide: 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane; 0.1%;

[0132] Antioxidants: 1076 and 168; 0.1% each;

[0133] Lubricant: PETS; 0.2%.

[0134] Example 9

[0135] The difference from Example 1 is that the amount of hyperbranched polyester is increased, and the raw materials include the following components in parts by weight:

[0136] PLLA: E190; 83.7%;

[0137] Branched PLLA: BPLLA-1; 5%;

[0138] PDLA: D070; 5%;

[0139] E-type glass flake: REFG-101; 5%;

[0140] Hyperbranched polyester: HyPer C181; 0.8%;

[0141] Peroxide: 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane; 0.1%;

[0142] Antioxidants: 1076 and 168; 0.1% each;

[0143] Lubricant: PETS; 0.2%.

[0144] Example 10

[0145] The difference from Example 1 is that the amount of hyperbranched polyester and peroxide is increased, and the raw materials include the following components in parts by weight:

[0146] PLLA: E190; 84.0%;

[0147] Branched PLLA: BPLLA-1; 5%;

[0148] PDLA: D070; 5%;

[0149] E-type glass flake: REFG-101; 5%;

[0150] Hyperbranched polyester: HyPer C181; 0.3%;

[0151] Peroxide: 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane; 0.3%;

[0152] Antioxidants: 1076 and 168; 0.1% each;

[0153] Lubricant: PETS; 0.2%.

[0154] Embodiment 11

[0155] The difference from Example 1 is that the type of raw material PLLA is changed, and the components in parts by weight are as follows:

[0156] PLLA: L175; 84.2%;

[0157] Branched PLLA: BPLLA-1; 5%;

[0158] PDLA: D070; 5%;

[0159] E-type glass flake: REFG-101; 5%;

[0160] Hyperbranched polyester: HyPer C181; 0.3%;

[0161] Peroxide: 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane; 0.1%;

[0162] Antioxidants: 1076 and 168; 0.1% each;

[0163] Lubricant: PETS; 0.2%.

[0164] Example 12

[0165] The difference from Example 1 is that the branched PLLA is replaced, and the raw materials include the following components in parts by weight:

[0166] PLLA: E190; 84.2%;

[0167] Branched PLLA: BPLLA-2; 5%;

[0168] PDLA: D070; 5%;

[0169] E-type glass flake: REFG-101; 5%;

[0170] Hyperbranched polyester: HyPer C181; 0.3%;

[0171] Peroxide: 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane; 0.1%;

[0172] Antioxidants: 1076 and 168; 0.1% each;

[0173] Lubricant: PETS; 0.2%.

[0174] Example 13

[0175] The difference from Example 1 is that the type of PDLA is changed, and the raw materials include the following components in parts by weight:

[0176] PLLA: E190; 84.2%;

[0177] Branched PLLA: BPLLA-1; 5%;

[0178] PDLA: D120; 5%;

[0179] E-type glass flake: REFG-101; 5%;

[0180] Hyperbranched polyester: HyPer C181; 0.3%;

[0181] Peroxide: 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane; 0.1%;

[0182] Antioxidants: 1076 and 168; 0.1% each;

[0183] Lubricant: PETS; 0.2%.

[0184] Embodiment 14

[0185] The difference from Example 1 is that the type of glass flakes is changed, and the raw materials include the following components in parts by weight:

[0186] PLLA: E190; 84.2%;

[0187] Branched PLLA: BPLLA-1; 5%;

[0188] PDLA: D070; 5%;

[0189] E-type glass flake: M01; 5%;

[0190] Hyperbranched polyester: HyPer C181; 0.3%;

[0191] Peroxide: 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane; 0.1%; Antioxidants: 1076 and 168; 0.1% each;

[0192] Lubricant: PETS; 0.2%.

[0193] Comparative Example 1

[0194] The raw materials include the following components in parts by weight:

[0195] PLLA: E190; 99.6%;

[0196] Antioxidants: 1076 and 168; 0.1% each;

[0197] Lubricant: PETS; 0.2%.

[0198] Comparative Example 2

[0199] The raw materials include the following components in parts by weight:

[0200] PLLA: E190; 89.2%;

[0201] PDLA: D070; 5%;

[0202] E-type glass flake: REFG-101; 5%;

[0203] Hyperbranched polyester: HyPer C181; 0.3%;

[0204] Peroxide: 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane; 0.1%; Antioxidants: 1076 and 168; 0.1% each;

[0205] Lubricant: PETS; 0.2%.

[0206] Comparative Example 3

[0207] The raw materials include the following components in parts by weight:

[0208] PLLA: E190; 94.2%;

[0209] Branched PLLA: BPLLA-1; 5%;

[0210] Hyperbranched polyester: HyPer C181; 0.3%;

[0211] Peroxide: 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane; 0.1%;

[0212] Antioxidants: 1076 and 168; 0.1% each;

[0213] Lubricant: PETS; 0.2%.

[0214] Comparative Example 4

[0215] The raw materials include the following components in parts by weight:

[0216] PLLA: E190; 84.2%;

[0217] Branched PLLA: BPLLA-1; 5%;

[0218] PDLA: D070; 5%;

[0219] E-type glass fiber: 534A; 5%;

[0220] Hyperbranched polyester: HyPer C181; 0.3%;

[0221] Peroxide: 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane; 0.1%;

[0222] Antioxidants: 1076 and 168; 0.1% each;

[0223] Lubricant: PETS; 0.2%.

[0224] Test results:

[0225] The materials of the embodiment and the comparative example were dried in a vacuum oven at 80°C for 4h, and the samples were prepared using an injection molding machine. The tensile strength was tested according to GB / T1040.22006, and the test speed of the 1A type specimen was 50mm / min; the cantilever beam impact strength was tested according to GB / T1843-2008; the melt mass flow rate was tested according to GB / T3682-2000, under the conditions of 190°C and 2.16Kg; the heat deformation temperature was tested according to GB / T1634 -2004, condition 0.45Mpa; heat treatment condition is 110℃ blast oven, heat deformation specimen and maximum warpage specimen (60mm*60mm*1mm specimen) are baked for 4min; the maximum warpage specimen of 60mm*60mm*1mm is placed on a flat table after heat treatment, and the distance between the highest point of the specimen and the table after deformation is measured, unit mm; the test results are shown in Tables 1 and 2 (wherein, " / " in Tables 1 and 2 indicates that the component is not contained).

[0226] T1 is the heat deformation temperature obtained by testing the specimen without heat treatment (heat treatment conditions: the specimen is baked in a forced air oven at 110°C for 4 minutes).

[0227] T2 is the heat deformation temperature obtained after the specimen is heat treated (heat treatment conditions: the specimen is baked in a forced air oven at 110°C for 4 minutes).

[0228] Table 1

[0229]

[0230] Table 2

[0231]

[0232] By comparing the test data of the embodiments and comparative examples in the above table, it can be seen that by adjusting the amount of toughening agent branched PLLA, the impact strength of the material can be increased, and the fluidity of the material can also be increased; by adjusting the amount of heat-resistant and anti-warping modifiers PDLA and glass flakes, the tensile strength and heat deformation temperature of the material can be improved, especially the heat deformation temperature and anti-warping performance of the material after heat treatment are improved; adding flow modifiers hyperbranched polyester and / or peroxide can significantly improve the melt index of the material, and the flow modifier has a synergistic effect with the heat-resistant modifier and the heat-resistant anti-warping modifier, which can significantly improve the heat resistance and anti-warping performance of the material.

[0233] Through the compound use of toughening agent, heat resistant agent, anti-warpage modifier and flow modifier, the fluidity of the material can be adjusted in a wide range, the heat resistance temperature and anti-warpage property can be increased, and the requirements of short PLA thin-wall injection molding cycle, heat resistance and anti-warpage of the product can be met.

[0234] The above is an exemplary description of the embodiments of the present invention. However, the protection scope of the present invention is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A composition, characterized in that Calculated by weight, it includes: 50-99% of polylactic acid, 1-20% of toughening agent, 0.5%-40% of heat-resistant modifier, 0.5%-30% of heat-resistant anti-warping agent, 0.01%-25% of flow regulator, 0.01%-1% of antioxidant and 0.01%-1% of lubricant.

2. The composition according to claim 1, characterized in that Calculated by weight, it includes: 75-95% of polylactic acid, 3-15% of toughening agent, 3%-20% of heat-resistant modifier, 3%-15% of heat-resistant anti-warping agent, 0.1%-15% of flow regulator, 0.1%-1% of antioxidant and 0.1%-1% of lubricant. Preferably, the composition comprises, by weight, 75-90% polylactic acid, 3-12% toughening agent, 3%-18% heat-resistant modifier, 3%-12% heat-resistant anti-warping agent, 5%-15% flow regulator, 0.1%-0.5% antioxidant and 0.1%-0.5% lubricant.

3. The composition according to claim 1, characterized in that The polylactic acid is PLLA, preferably high optical purity PLLA, L optical purity ≥ 98%, and melt index 1-20 (190° C., 2.16 kg). Preferably, the toughening agent is branched polylactic acid PLLA, with a number average molecular weight of 30,000-150,000 and a branching degree g'≤0.

8.

4. The composition according to any one of claims 1 to 3, characterized in that The heat-resistant modifier is one of PDLA and glass flakes or a combination thereof; the PDLA is poly (d-lactic acid), preferably with a D optical purity of ≥98% and a melt index of 3-150 g / 10 min (190° C., 2.16 kg).

5. The composition according to any one of claims 1 to 4, characterized in that The heat-resistant modifier is a compound of PDLA and glass flakes.

6. The composition according to any one of claims 1 to 5, characterized in that The flow regulator is one of branched polylactic acid, hyperbranched polyester, and a combination of two or three thereof; preferably, the molecular weight of the branched polylactic acid is 30,000-150,000, and the degree of branching g' is ≤0.8; the peroxide is 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane; the acid value of the hyperbranched polyester is >300 mg KOH / g, preferably a branched aromatic polyester, such as HyPer C181, which has an acid value of 400 mg KOH / g.

7. The composition according to any one of claims 1 to 6, characterized in that The flow regulator is a combination of branched polylactic acid, hyperbranched polyester and peroxide. Preferably, the lubricant is an alkyd ester lubricant. Preferably, the composition comprises, by weight: 90% of Hisun E190 and / or Total L17578, 3-12% of BPLLA-1 and / or BPLLA-2, 4-20% of heat-resistant modifier and heat-resistant anti-warping agent, the heat-resistant modifier and heat-resistant anti-warping agent are at least one of D070, D120, Japanese NSG REFG-101, and Japanese NSG MEG160FY-M01, 0.1%-0.4% of a composition of HyPer C181 and 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 0.1%-0.5% of antioxidant 1076 and / or antioxidant 168, and 0.1%-0.5% of lubricant PETS. Preferably, the composition comprises, by weight: 90% of Hisun E190 and / or Total L17578, 5-10% of BPLLA-1 and / or BPLLA-2, 5-20% of heat-resistant modifier and heat-resistant anti-warping agent, the heat-resistant modifier and heat-resistant anti-warping agent are a combination of D070 and / or D120 and at least one of Japanese NSG REFG-101 and / or Japanese NSG MEG160FY-M01, 0.1%-0.4% of a composition of HyPer C181 and 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 0.1%-0.5% of antioxidant 1076 and / or antioxidant 168, and 0.1%-0.5% of lubricant PETS.

8. A method for preparing a degradable composite material for thin-wall injection molding using the composition of any one of claims 1 to 7, characterized in that: The method comprises the following steps: polylactic acid, a toughening agent, a heat-resistant modifier, a heat-resistant anti-warping agent, a flow regulator, an antioxidant and a lubricant are uniformly mixed according to a proportion, and then extruded and granulated. Preferably, the method comprises: drying PLLA and PDLA in a vacuum oven, and then fully mixing the above substances in a high-speed mixer according to the above ratio, and then melt-extruding and granulating them through a twin-screw extruder to obtain a thin-wall injection molding PLA composition; Among them, the temperature of each section of the barrel is: the temperature of the second section barrel is 135℃, the temperature of the third, fourth and fifth sections barrel is 200℃, the temperature of the sixth, seventh, eighth and ninth sections barrel is 190℃, the temperature of the ninth, tenth and eleventh sections barrel is 185℃, the head temperature is 180℃, the feeding frequency is 50 Hz, and the main engine speed is 200 rpm.

9. The degradable composite material for thin-wall injection molding prepared by the method of claim 8.

10. The degradable composite material for thin-wall injection molding according to claim 9, characterized in that: The degradable composite material for thin-wall injection molding is used for preparing disposable thin-wall products such as lunch boxes and milk tea cups.

Citation Information

Patent Citations

  • Starch-based biodegradable plastic master batch special for thin-wall injection molding and preparation method thereof

    CN112409646A

  • Full-biodegradable material for thin-wall injection molding and preparation method thereof

    CN112694727A